Analysis and implementation of peak armature current (Imax) of a chopper-fed DC-DC motor drive in DCM - Abdullah, Mohamad Nazir; Mohamed Hariri, Muhammad Hafeez; Mat Desa, Mohd Khairunaz; Mamat, Mohd Nadzri; Kaharuddin, Suardi (Institute of Advanced Engineering and Science, 2025)
At low frequencies of operation in a chopper-fed direct current (DC) motor drive, the armature current may become discontinuous thus the controller operates in discontinuous conduction mode (DCM). Since the minimum armature current is zero in DCM, the analysis of peak armature current (Imax) is to investigate the ripple content in armature current at different values of duty cycle which will help in decreasing the peaky current of DC motor during operation. The simulation was carried out using MATLAB-Simulink software and the laboratory setup was based on Atmega 328 microcontroller board. In this paper, the theoretical and experimental analysis of peak armature current were performed at fix low frequency in DCM and variable duty cycles to provide full control of DC motor speed. The results show that the peak armature current changes with the change of duty cycles and its magnitude is decreased almost 50% at higher duty cycle values.